Desenvolvimento dos municípios mineiros: uma análise da lei Robin Hood - Gomes, Carina Antonellie Batista (2018)
Socioeconomic Development is the qualitative analysis of aspects related to the population, such as access to better social services such as health and education. This definition may or may not be linked to the concept of economic growth, since more financial resources allow investments in areas related to quality of life. To ensure that all government entities are able to provide development, Federalism enables the creation of resource transfer tools among them, in order to equate the provision of public services with the needs of the population. In order to obtain funds, ICMS stands out in the Brazilian states, whose transfer is estimated by different policies. In Minas Gerais, onlendings are made based on criteria stipulated by the Robin Hood Law (LRH), whose premise is the redistribution of income among municipalities, rewarding those who invest in certain sectors. With the objective of analyzing the improvement of the social conditions of the municipalities of Minas Gerais, this study evaluates the development of the socio-economic indicators IMRS, IRFS, HDI-M and PIB-M, and their relation with the pass-through criteria. The study sampled all Minas Gerais municipalities from 2002, respecting the available time interval for each indicator, evaluating the performance of municipalities, and highlighting those most affected by the variations of the indicator. This stage is developed with k-means clusters and subjected to analyzes based on Kruskal-Wallis test and Bonferroni adjustment. The relationship between LRH transfers and socioeconomic indicators is also studied, aiming at obtaining a regression model using Spearman correlation and the backward method, as well as the MMQ and the application of dummy variables. The research indicates average growth of the indicators, but without a significant reduction in the income distribution, and that this growth does not have a relation with the LRH, denoting the influence of other reasons, such as changes in the political management and increase of resources from other sources.